Politeness Principles In “Persuasion” Movie - Susi Anggraeni (Universitas Veteran Bangun Nusantara, 2021)
The aims of this study is finding and describing politeness principle in Persuasion movie adopted from one of famous novels written by Jane Austen. This research was a descriptive qualitative research. The data of this research were words, phrases and sentences on the dialogues uttered by the characters which generated politeness principle. The techniques of collecting data used in this research were documentation and content analysis. The procedure of the research obtained from collecting the data, giving code to each data, displaying the data and drawing the conclusion and the researcher used theory triangulation. The research found 23 data in Persuasion movie that consisted of: 1) tact maxim (6 or 26%), 2) approbiation maxim (4 or 17%), 3) generosity maxim (3 or 13%), 4) modesty maxim (3 or 13%), 5) agreement maxim (6 or 26%) and sympathy maxim (1 or 6%) which tact maxim and agreement maxim found as the dominant type of politeness principle in Persuasion movie. The conclusion of this research were: 1) there are six types of politeness principle which specifically discussed in this research and there were 23 data collected from those six types. 2) the researcher drawing the data into percentage to make it easier to saw which types of those six maxim were become the dominant type which founded. Factually, there are a lot of discussion dialogue which contains agree and disagreement and it requires the participants (speaker and listener) minimize cost and maximize benefit to other as the reason why Tact Maxim and Agreement Maxim become the most dominant type of politeness principle that are used in Persuasion movie.